2011
DOI: 10.1029/2010jb008176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CO2on the long-term chemomechanical behavior of an oolitic limestone

Abstract: [1] In order to study the long-term mechanical and petrographical evolutions of a carbonate rock (oolitic limestone) during storage of CO 2 , CO 2 injection tests were performed in triaxial cells at temperature and mechanical stresses (isotropic and deviatoric) corresponding to the depth of the Dogger carbonate reservoirs of the Paris basin (∼800 m). We used a specific "flow-through" triaxial cell which allowed us to measure very low strain rates in both axial and lateral directions, while ensuring the sealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 81 publications
(162 reference statements)
2
39
0
1
Order By: Relevance
“…As a result, compaction and compaction rates increase (Grgic, 2012;Le Guen et al, 2007;Liteanu et al, 2012;Vanorio et al, 2011), while a decrease in elastic properties (Madland et al, 2006;Vialle and Vanorio, 2011) and rock strength (Madland et al, 2006) is observed.…”
Section: Effect Of Co 2 /Brine/rock Interactions On Mechanical Propermentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, compaction and compaction rates increase (Grgic, 2012;Le Guen et al, 2007;Liteanu et al, 2012;Vanorio et al, 2011), while a decrease in elastic properties (Madland et al, 2006;Vialle and Vanorio, 2011) and rock strength (Madland et al, 2006) is observed.…”
Section: Effect Of Co 2 /Brine/rock Interactions On Mechanical Propermentioning
confidence: 99%
“…Studies on the effect of CO 2 -saturated fluids on mechanical and transport properties of carbonate rocks and aggregates (Grgic, 2012;Le Guen et al, 2007;Liteanu et al, 2012;Madland et al, 2006;Vialle and Vanorio, 2011) show dissolution of the carbonate phases, leading to the creation of flow channels (Le Guen et al, 2007;Madland et al, 2006) and a significant increase in porosity and permeability (Le Guen et al, 2007;Vanorio et al, 2011;Vialle and Vanorio, 2011). As a result, compaction and compaction rates increase (Grgic, 2012;Le Guen et al, 2007;Liteanu et al, 2012;Vanorio et al, 2011), while a decrease in elastic properties (Madland et al, 2006;Vialle and Vanorio, 2011) and rock strength (Madland et al, 2006) is observed.…”
Section: Effect Of Co 2 /Brine/rock Interactions On Mechanical Propermentioning
confidence: 99%
See 3 more Smart Citations